Stres psikologis dan gejala kekambuhan gastritis kronis pada lansia: Studi cross-sectional - Meiriyanti Meiriyanti; Rahma Elliya; Triyoso Triyoso (Holistik Jurnal Kesehatan, 2022)
Background : Elderly people with some chronic conditions have a higher risk of experiencing gastric acid disease. Based on the results of the survey conducted on December 26, 2018 - January 2, 2019, there were 10 elderly patients diagnosed with gastritis, of which 70% revealed, often angry, often had difficulty sleeping, found it difficult to relax, irritable and as much as 30% revealed late eat and like to eat foods that are high in fat.Purpose: Knowing the relationship between psychological stress and symptoms of chronic gastritis recurrence in the elderlyMethod: Type of quantitative research, the study design was cross-sectional. The population of this study is the elderly. Independent variables: psychological stress and dependent variable: symptoms of chronic gastritis recurrence. Collecting data with questionnaires and medical records taken on  March - April 2019. Data analysis is univariate (frequency distribution) and bivariate using the chi-square test.Results: Finding of 66 (60.6%) respondents had symptoms of chronic gastritis recurrence and psychological stress 56 (51.4%) (p-value = 0,000 OR 6,234).Conclusion: There is a relationship between psychological stress and symptoms of chronic gastritis recurrence in the elderly in the UPTD Sri Bhawono,Suggestions: The management of the Public health center to provide information to patients about the factors that influence the symptoms of chronic gastritis recurrence, especially psychological stress, and provides a psychologist consultant.Keywords: Psychological stress; Symptoms; Gastritis; ElderlyPendahuluan: Lansia dengan beberapa kondisi kronis memiliki risiko lebih tinggi untuk mengalami penyakit asam lambung. Berdasarkan hasil prasurvey yang dilakukan tanggal 26 Desember 2018 – 2 Januari 2019, terdapat  10 pasien usia lanjut dengan diagnosa gastritis, dimana sebanyak 70% mengungkapkan, sering marah, sering susah tidur, merasa sulit untuk bersantai, mudah tersinggung dan sebanyak 30% mengungkapkan sering telat makan dan suka mengkonsumsi makanan yang berlemak tinggi.Tujuan: Mengetahui hubungan stres psikologis dengan gejala kekambuhan gastritis kronis pada lansiaMetode : Jenis penelitian kuantitatif, dengan desain penelitian cross sectional. Populasi penelitian ini adalah lansia. Variabel bebas: stres psikologis dan variabel terikat: gejala kekambuhan gastritis kronis. Pengumpulan data dengan kuesioner dan rekam medis yang diambil pada bulan Maret – April 2019. Analisis data dilakukan secara univariat (distribusi frekuensi) dan bivariat menggunakan uji chi-square.Hasil : Didapatkan 66 (60,6%) responden memiliki gejala kekambuhan gastritis kronis dan stres psikologis 56 (51,4%) (p-value = 0,000 OR 6,234).Simpulan: Didapatkan hubungan stres psikologis dengan gejala kekambuhan gastritis kronis pada lansia di UPTD Sri Bhawono,Saran: Manajemen Puskesmas memberikan informasi kepada pasien tentang faktor-faktor yang mempengaruhi gejala kekambuhan gastritis kronis terutama stres psikologis, dan menyediakan konsultan psikolog.